Evaluation of Wound Healing Potential of Root Bark Extract of Berberis aristata and Molecular Docking Analysis of Berberis Phytoconstituents - Shrivastav, Alankar; Mishra, Arun K.; Gupta, Ashessh Kumar (Current Drug Discovery Technologies, 2023)
Introduction: The root bark of Berberis aristata has been utilized by indigenous peoples for wound treatment for centuries. The mature root barks are crushed into a paste and applied to the wound's surface. Objective: The focus of this research is to analyse the wound healing activities of an ethanolic extract of Berberis aristata, as well as to use molecular docking to establish the likely mechanism of the potent phytochemical. There is no scientific evidence to support the usage of root bark extract of Berberis aristata. Methods: The Herbal ointment, which comprises (1%, 2%, and 4% w/w) ethanolic extract of root bark, was developed to test the wound healing ability of incision and excision wounds, and the molecular mechanism was established using Auto-Dock software. Results: Epithelization stage, wound index, % wound contraction area, hydroxyproline content, DNA estimate, and histopathological assessments were performed on the incision wound model. Tensile strength was assessed in an excision wound model. TLC was used to identify the samples after successive extractions with different solvents based on polarity. Conclusion: Berberine and tetrahydropalmatine were major active phytoconstituent found in root barks of Berberis aristata as secondary metabolites. Animals treated with 4% w/w formulation demonstrated considerable wound contraction, epithelization time, and wound index in the excision model. In contrast, to control and standardize the concentrations of hydroxyproline, total amino acids, and DNA in recovering tissue were higher. At 4% w/w extract formulation, the parameters studied indicated a substantial result. Berberine and tetrahydropalmatine, active metabolites which are present in the ethanolic extract of Berberis aristata, were found to be responsible for wound healing. Based on ligand interactions, the findings verified Berberis aristata ethnomedicinal claim in a wound healing capacity.
Keywords: Berberis aristata